2015
DOI: 10.1002/cphc.201500485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Formation of Silver Nanoparticles by using a Seed‐Free Photochemical Method under Sodium‐Lamp Irradiation

Abstract: Silver nanoparticles can be prepared by using a seed-free photo-assisted citrate reduction method under the irradiation of a sodium lamp. Under the same irradiation intensity, bath temperatures are crucial in influencing the reaction rate, morphologies of final products, and shape evolution of the silver nanostructures. For example, when the bath temperature is 80 °C, the product yields of silver nanoplates, nanorods, and nanodecahedra are 38±6 %, 35±10 %, and 12±8 %, respectively. However, when the bath tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…This observation indicates that plate-like or rod-liken anostructures are the kinetically favored products but not the thermodynamically favored products in this experimental condition. [38] These kinetically favored products play the roles of intermediates that were formed first and then dissolved graduallyt op rovides ilver elements for the growth of seeds to form icosahedral NPs.…”
Section: Comparison Between the Photoassisted Tartrate Reduction Methmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation indicates that plate-like or rod-liken anostructures are the kinetically favored products but not the thermodynamically favored products in this experimental condition. [38] These kinetically favored products play the roles of intermediates that were formed first and then dissolved graduallyt op rovides ilver elements for the growth of seeds to form icosahedral NPs.…”
Section: Comparison Between the Photoassisted Tartrate Reduction Methmentioning
confidence: 99%
“…[38] Compared with plasmon-mediated reactions, the photoassisted citrate reduction method has the advantages of fewer processes, higherr eproducibility,a nd higher throughput. [37,38] It has been found that different reduction agentsw ill strongly affect the shape distributionsa nd product yields of AgNPsb yu sing direct chemical reduction methods. [39] However,n ot many photoreduction reagents other than sodium citrate have been used or studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the other nanoparticles formation methods obtained by other research studies which illustrated the nanoparticles formation of different sizes and interparticle separation as the temperature increased. Also, those methods required subsequent process of annealing temperature as an additional process that showed indirect deposition on the substrate surface [35][36][37][38]. Moreover, the substrate temperature provides sufficient surface mobility to the deposited Ag nanoparticles for diffusion into their growth sites and coalescing to form larger particles [39].…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…Thus, the productivity of AgNPs was dependent on the temperature conditions; the higher the temperature, the more productivity. Although, temperature influences the formation and productivity of AgNPs [16], the role of the reaction temperature in the growth rate of AgNPs is yet to be well understood [17].…”
Section: Ultraviolet-visible (Uv-vis) Absorption Spectroscopymentioning
confidence: 99%